Statistical optimization of process parameters for the production of citric acid from oil palm empty fruit bunches - Bari, Md. Niamul; Alam, Md. Zahangir; Muyibi, Suleyman Aremu; Jamal, Parveen; Al-Mamun, Abdullah (Academic Journals, 2010)
In this study, optimization of process parameters such as moisture content, incubation temperature and initial pH (fixed) for the improvement of citric acid production from oil palm empty fruit bunches through solid state bioconversion was carried out using traditional one-factor-at-a-time (OFAT) method and response surface methodology (RSM). The possible optimum level of moisture content, incubation temperature, and initial pH were found from the OFAT study to be 70%, 30 - 32oC and 5.5 - 8, respectively. The optimum moisture content of 70.3% (v/w) and incubation temperature of 33.1°C with initial pH of 6.5 gave the maximum production of citric acid (369.16 g/kg of dry EFB). The analysis of variance (ANOVA) of the statistical optimization using central composite design showed that moisture content (p<0.001) and incubation temperature (p<0.0001) as well as the interaction of these two parameters were highly significant for the citric acid production.